The English Blending words in Tempo English Magazine - Rizky Gumilar (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
Blending offers a unique and unusual character which is frequently used by mass because of its creativity and this study aims to figure out the pattern of English blending words in Tempo English Magazine created and the meanings of those blending words. The study found that the complex words show the pattern. The pattern of those analysis complex words are categorized into AB + CD =AD. These patterns are based on Plag’s theory about blending words. The meaning of those complex words was built based on the first and the second words. It follows the pattern of AD, namely the first term (A) and the last term (D) are combined. The eight blending words discussed are not common in English itself. It is because these English complex words have been domesticated by Indonesian’s terms.Keywords: Blending, Words, Tempo, English, Magazine, Morphology